Teachers’ Opinions on Kindergarten Admission Standards: Risks to Toddler Well-Being? - Loudová Stralczynská, Barbora; Lipnicka, Milena; Chytrý, Vlastimil (Revija za elementarno izobraževanje, 2025)
The aim of this paper is to present the opinions of teachers on the standards for admitting toddlers to kindergartens in the Czech Republic and Slovakia, and to discuss these standards in relation to the risks to children’s well-being. Opinions were obtained through a quantitative survey among teachers from the Czech Republic (n=574) and Slovakia (n=593) in 2023. Results showed that most teachers do not support the admission of children under three to kindergartens. They conditionally support admission based on self-care skills, hygiene habits, and socio-emotional independence, which do not match typical toddler development, posing pressure on the child and family.